1996
DOI: 10.7326/0003-4819-125-6-199609150-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Universal Use of Gloves and Gowns with That of Glove Use Alone on Acquisition of Vancomycin-Resistant Enterococci in a Medical Intensive Care Unit

Abstract: Universal use of gloves and gowns was no better than universal use of gloves only in preventing rectal colonization by vancomycin-resistant enterococci in a medical intensive care unit of a hospital in which vancomycin-resistant enterococci are endemic. Because the use of gowns and gloves together may be associated with better compliance and may help prevent transmission of other infectious agents, this finding may not be applicable to outbreaks caused by single strains or hospitals in which the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
198
3
8

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(211 citation statements)
references
References 0 publications
2
198
3
8
Order By: Relevance
“…Nevertheless, organ transplantation, blood supply and hospital infrastructure renovations are also recognized as other causes of nosocomial infections. 2 Among them and not surprisingly, nosocomial pneumonia is currently reported as the second higher cause of nosocomial infections, corresponding to about 18% of the total of nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, organ transplantation, blood supply and hospital infrastructure renovations are also recognized as other causes of nosocomial infections. 2 Among them and not surprisingly, nosocomial pneumonia is currently reported as the second higher cause of nosocomial infections, corresponding to about 18% of the total of nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the presence of a VRE-colonized patient in the previous 2 weeks or a previous positive environmental culture were highly predictive for VRE acquisition by the subsequent occupant of the room 13 . In our study, the majority of the patients (73%) were cared for in just 4 wards and, conversely to the reported literature [14][15][16] , with the exception of the Trauma unit, these wards were not involved in intensive care. Furthermore, these same wards had previous problems with the sewage system, including disruption of the sewer lines, which may have contributed to the outbreak.…”
Section: Resultsmentioning
confidence: 46%
“…13 Srinivasan et al suggest that the differences in the findings of the two studies may be due to the low prevalence of environmental contamination (6.3%) in the medical intensive care unit studied by Slaughter et al and also due to differences in study design. In the latter study, the two populations studied (gloves versus gowns and gloves) were present in the medical intensive care unit at the same time, in contrast to the study of Srinivasan et al in which the two populations were studied sequentially.…”
mentioning
confidence: 91%
“…45 VRE have been shown to survive for prolonged periods of time in the environment, and an outbreak in a burn unit recurred after 5 weeks from an electrocardiogram lead that had been contaminated by a colonized patient 38 days before VRE was cultured from the lead on the second patient. 6^ Risk factors for acquisition of VRE include treatment with vancomycin 910 and cephalosporins, 1112 receipt of enteral feedings, 1113 sucralfate, 13 or antacids, 810 colonization pressure, 11 and proximity to previously unisolated patients with VRE. 14 On the basis of the epidemiology of VRE, in 1995 the Hospital Infection Control Practices Advisory Committee (HICPAC) of the CDC published recommendations for preventing the spread of vancomycin resistance.…”
mentioning
confidence: 99%